Supernova : Art of the 1990's from the Logan Collection - Benezra, Neal; Cameron, Dan; Cruz, Amada; Grynsztejn, Madeleine; Kim, Clara; Logan, Kent; Logan, Vicki; McDowell, Tara; Morgan, Jessica; Rugoff, Ralph; Siegel, Katy (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2003)
Ackermann, Franz ; Antoni, Janine ; Close, Chuck ; Crewdson, Gregory ; Currin, John ; Demand, Thomas ; diCorcia, Philip-Lorca ; Dumas, Marlene ; Edmier, Keith ; Emin, Tracey ; Essenhigh, Inka ; Fang Lijun ; Fritsch, Katharina ; Gober, Robert ; Gonzalez-Torres, Felix ; Hirst, Damien ; Hume, Gary ; Kahlhamer, Brad ; Kentridge, William ; Kuri, Gabriel ; Ligon, Glenn ; Majerus, Michel ; Marshall, Kerry James ; Morimura, Yasumasa ; Morris, Sarah ; Mueck, Ron ; Muniz, Vik ; Muñoz, Juan ; Murakami, Takashi ; Nara, Yoshitomo ; Ofili, Chris ; Rauch, Neo ; Scheibitz, Thomas ; Schütte, Thomas ; Shonibare, Yinka ; Simmons, Gary ; Smith, Kiki ; Sugimoto Hiroshi ; Taylor-Wood, Sam ; Wall, Jeff ; Whiteread, Rachel ; Xu Yihui ; Yanagi, Yukinori ; Yuskavage, Lisa ; Zhang Huan
Supernova : Art of the 1990s from the Logan Collection, SFMOMA (San Francisco Museum of Modern Art), San Francisco, 2003-12-13. 2004-05-23
boek